2015
DOI: 10.1016/j.drugalcdep.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dronabinol during detoxification and the initiation of treatment with extended release naltrexone

Abstract: Background Evidence suggests that the cannabinoid system is involved in the maintenance of opioid dependence. We examined whether dronabinol, a cannabinoid receptor type 1 partial agonist, reduces opioid withdrawal and increases retention in treatment with extended release naltrexone (XR-naltrexone). Methods Opioid dependent participants were randomized to receive dronabinol 30 mg/d (n=40) or placebo (n=20), under double-blind conditions, while they underwent inpatient detoxification and naltrexone induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 34 publications
1
86
0
4
Order By: Relevance
“…Newer protocols focused on identifying optimal doses and treatment durations of buprenorphine, naltrexone, and clonidine to shorten induction periods, while minimizing the severity of withdrawal. Major changes to earlier protocols involved reducing buprenorphine treatment to 1–2 days, shortening to 1 day the “washout” period before starting naltrexone, and decreasing the first dose of naltrexone from 12.5 to 3 mg, with supportive medications, usually standing doses of clonidine and clonazepam administered at frequent dosing intervals 51, 52, 53, 54, 55, 56, 57. A 2017 study comparing outpatient detoxification regimens showed that an oral naltrexone‐assisted detoxification regimen, compared with a descending buprenorphine taper followed by a 7‐day washout period, was more likely to lead to successful XR‐NTX induction (56% vs. 33%) and a second XR‐NTX dose (50% vs. 27%) 58…”
Section: Historical Perspective On Clinical Management Of Opioid Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Newer protocols focused on identifying optimal doses and treatment durations of buprenorphine, naltrexone, and clonidine to shorten induction periods, while minimizing the severity of withdrawal. Major changes to earlier protocols involved reducing buprenorphine treatment to 1–2 days, shortening to 1 day the “washout” period before starting naltrexone, and decreasing the first dose of naltrexone from 12.5 to 3 mg, with supportive medications, usually standing doses of clonidine and clonazepam administered at frequent dosing intervals 51, 52, 53, 54, 55, 56, 57. A 2017 study comparing outpatient detoxification regimens showed that an oral naltrexone‐assisted detoxification regimen, compared with a descending buprenorphine taper followed by a 7‐day washout period, was more likely to lead to successful XR‐NTX induction (56% vs. 33%) and a second XR‐NTX dose (50% vs. 27%) 58…”
Section: Historical Perspective On Clinical Management Of Opioid Withmentioning
confidence: 99%
“…Initiation of treatment with XR‐NTX shortly after completion of opioid withdrawal, or lack of confirmation of the absence of current opioid dependence or recent buprenorphine use, may result in protracted withdrawal‐like symptoms for several weeks 30. Symptoms can include sleep disturbances, low energy, anxiety, irritability, and diarrhea that slowly resolve over days to weeks 52, 57. To alleviate protracted withdrawal, several medication strategies have been proposed, including methylphenidate85 and quetiapine,86 and cannabis may also have a therapeutic benefit 57…”
Section: Current Approach To Treatment Of Opioid Use Disorder: Choosimentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a randomized, double-blind, placebo-controlled, phase III trial has shown that cannabinoids may be useful add-on analgesic drugs for patients with opioid-refractory cancer pain (Portenoy et al, 2012). Although more exhaustive follow-on controlled human studies are indeed necessary, this evidence strongly supports that cannabinoids might be combined with opioids for benefiting patients with pain -and perhaps other diseases (Bisaga et al, 2015;Hurd et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, patients who regularly smoked cannabis achieved higher retention rates in the detoxification program compared with noncannabis users. 17 Cellular studies of agonist co-activation of CB1 and mu opioid receptors produced a smaller response than activation of either receptor independently. 11 Partial opioid receptor activation may serve to explain the decreased incidence of withdrawal effect that our patient experienced when tapering off opioids, similar to the opioid agonist-antagonist effect of buprenorphine.…”
Section: Discussionmentioning
confidence: 99%